Corneal Bee Sting Controlled with Early Surgical Intervention and Systemic High-Dose Steroid Therapy - Jung-Hoon Kim; Moosang Kim; Seung-Jun Lee; Sang Beom Han; Joon Young Hyon (Case Reports in Ophthalmological Medicine)
A 34-year-old Asian woman presented with painful corneal bee sting. Examinations revealed severe corneal swelling with stinger stuck in deep stroma and endothelial cell loss. She was treated with early surgery including stinger removal and anterior chamber irrigation combined with systemic high-dose steroid therapy. Vision and corneal clarity was recovered in 5 days and no additional corneal endothelial damage was observed. This report suggests that early surgical intervention and high-dose steroid therapy appear to be a useful option in the treatment of corneal bee sting.